A Plea For Iraqi National Cancer Center And Hospital - Alali, Neamah M. (Scientific Journal of Medical Research, 2018)
I had the opportunity of being a member of a group training in clinical oncology course in the National Cancer Center and Hospital in Tokyo-Japan , Which lasted for four months, this was arranged for post-graduate doctors of high qualifications in different specialties : general surgery, oncology, radiotherapy, chemotherapy, general medicine ,pediatrics , gynecology and obstetrics sponsored by JICA (Japan International Cooperation Agency). The number of the group was eleven, from: Iraq, Brazil, Argentine, Korea, Indonesia, Thailand, Taiwan, Malaysia, Panama and Colombia. We were all impressed by what we have witnessed in that center and the hospital with respect to diagnostic means and treatment protocols for all types of cancers in addition to research work on animals and the palliation for advanced cases of cancer. As a general surgeon I really saw ideal cancer surgery and cancer surgeons who were Organ Surgeons for different cancers. Such centers and hospitals are existing in many developed and developing countries.